PENGARUH PERTUMBUHAN PENJUALAN, STRUKTUR AKTIVA, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL (Studi Empiris pada perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2020 -2024) - Hanafi, Ahmad; Priyanto , Sugeng (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
The consumer non-cyclical sector in Indonesia has continued to demonstrate a growing contribution to the national economy,given that this sector is directly related to the provision of goods needed by the community on a daily basis. This study aims to determine the partial effects of Sales Growth, Asset Structure, Company Size, and Profit on Capital Structure. The population determination technique used non-probability sampling, specifically purposive sampling, with a research pupulation of 129 companies in the non-cyclical consumer sector and a research sample of 74 companies in the non-cyclical consumer sector, with analysis using multiple linear regression through SPSS version 27 and Microsoft Office 2024. The results indicate that Sales Growth does not affect Capital Structure, Asset Structure has a positive and significant effect on Capital Structure, Company Size does not affect Capital Structure, and Profitability has a negative and significant effect on Capital Structure